Book reviews: "Tom Richmond, General topology. An introduction", de Gruyter, 2020, ISBN 978-3-11-068656-2/pbk; 978-3-11-068657-9/ebook, xi + 314 pages. - COBZAȘ, S. (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The specific feature of this introductory text on general topology is the insistence on the relations between topology and order, with emphasis on the so called asymmetric topologies, meaning topologies in the non T1 setting.